Onde estavam as freguesias goianas até 1783? - Vinicius Sodré Maluly (Confins)
This paper proposes a study on the ecclesiastical structure of the Captaincy of Goyaz until the year of 1783. The study, using data extracted from the "Notícia Geral da Capitania de Goiás", proposes an approach methodologically inserted in Historical Geography with an employment of information techniques and quantitative analysis. On this procedural apparatus, the elaboration of a digital cartography allows the comprehension of elements that are pertinent to the "freguesias goianas" (or parishes), to their chapels and the dioceses that contained this broad territory of Portuguese America. Location factors were discussed, along with other space-associated parameters, such as the jurisdiction of these "freguesias", the demographic composition of the region and the frontiers that were made visible with these graphical elaborations. Lastly, quantitative analytics were extracted aiming to apprehend established trends over the gathered data, in reference to demography and also to the distance between each chapel and its "freguesia". Certain understandings were proposed on the research of the eighteenth century Goyaz, all provided by the technical and methodological elaboration indicated in this paper.